RETRACTED: Assessing the Nexus Between Green Economic Recovery, Green Finance, and CO2 Emission: Role of Supply Chain Performance and Economic Growth - Zhong, Weishun; Zong, Like; Yin, Weihua; Ali, Syed Ahtsham; Mouneer, Salma; Haider, Jahanzaib (Frontiers in Environmental Science, 2022)
Environmentalists are more concerned with the environment in this age of industrialization, and they are continually interested in researching factors that can facilitate the transition towards sustainability. This study applies an econometric technique called the panel Generalized Method of Moments generalized moments to analyze green finance and renewable energy’s impact on CO2 emissions from 2010 to 2019. According to the findings, green finance has a significant negative and positive impact on carbon emissions and green economic recovery. In addition, the results showed that logistics operations use energy and fossil fuel, and the findings also showed that the amount of fossil fuel and non-green energy sources creates a significant harmful effect on the environmental sustainability, in addition to having a negative impact on economic growth. Inadequate transportation-related infrastructure and logistics services are other significant contributors to CO2 and overall emissions of greenhouse gases. According to the findings, sustainable energy development can be advanced by fostering the growth of green finance. This can be accomplished by employing a variety of metrics that pertain to the three dimensions of economic development, financial development, and environmental development.